Evaluation of the macroeconomic stability of Central and Eastern European countries with a view toward their membership in the European Union: Multidimensional risk analysis - Jacek Pera (Comparative Economic Research. Central and Eastern Europe, 2016)
The economies of European countries have been undergoing constant turbulence for several years. This is the consequence of a range of factors, in particular: the 2007 crisis; violations of the convergence criteria and fiscal discipline; problems with the liquidity of international financial markets; depreciation of the euro currency; increasing unemployment in European Union Member States; the slow increase in productivity in the majority of EU economies; growing indebtedness of public finance sectors; problems with retirement schemes - in particular with correlation between their effectiveness and unemployment and low rate of natural increase. Thus, the author posits that it is important to analyse the key aspects related to these economic parameters which may affect this process in a significant way and decide the risk of its occurrence. This is the assumed aim of this work. The work shows the results of the author's own study, carried out with the use of different methods, such as the macroeconomic stabilisation pentagon, the Scoreboard, and Spearman's rank correlation coefficient. The variety of test methods employed results on one hand from the problem's complexity, and on the other from a profound analysis of all dependencies and risks resulting from this complexity. The conducted study shows that there is a significant correlation between the Scoreboard parameter imbalances and the intensity of crisis phenomena in case of violations of the acceptable thresholds in terms of current account balance, net international investment position, export market shares, nominal unit labour costs, real house prices, private sector debt, government debt, and the unemployment rate. The imbalances of these eight indicators may form an adverse macroeconomic environment favouring the occurrence of intense crisis phenomena, which means that they should be subject to special monitoring. The shapes of the macroeconomic stabilisation pentagon for CEEC economies in 2014 shows that none of the analysed countries is characterised by total filling of the pentagon. This means that the economic situation in these countries is not stable and requires constant monitoring. The figures related to all analysed indicators, apart from GDP, are characterised by a flattened shape, which is characteristic for such a situation.
Keywords: 330; stability; risk; imbalance; destabilisation; divergence